PENGARUH MODEL TGT (TEAMS GAMES TOURNAMENT) BERBASIS ICT TERHADAP HASIL BELAJAR SISWA KELAS V DI SD NEGERI 106865 BANDAR PAMAH - Saragih, Putri Yani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model based on ICT on the learning outcomes of fifth-grade students at SD Negeri 106865 Bandar Pamah in the subject of science, particularly on the topic of ecosystems and food chains. The research used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 17 students selected by total sampling. The instrument was a 15-item multiple-choice test, which had been validated for reliability and item difficulty. Data analysis showed that the average pretest score was 54.06 and the posttest score was 76.88. The average N-Gain score was 0.50, categorized as moderate. Normality tests showed the data were normally distributed, and the paired t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. It can be concluded that the ICT-based TGT learning model positively affects students' learning outcomes. This model is recommended as an innovative learning strategy in elementary schools to improve learning achievement and student engagement.